Characteristics of the menstrual cycle and hormonal contraceptive use in elite Spanish basketball players - Crespo, P.; Herranz, N.; Estella, V.; Morencos, E.; Herranz, M.; Rodas, G. (Frontiers in Sports and Active Living, 2025)
Introduction: Previous research has shown how menstrual-related symptoms (e.g., abdominal cramps, tiredness/fatigue) can limit athletes` ability to train. Nonetheless, the specific characteristics of the menstrual cycle (MC) and their relationship with performance, well-being, and injuries in athletes are not well understood. This cross-sectional study aimed to better understand the characteristics of the MC (menarche, length, dysmenorrhea, amenorrhea, etc.) and the use of hormonal contraceptives among the elite Spanish basketball players.